The effect of Pilates exercises on sleep quality and fatigue among female students dormitory residents - Azam Amzajerdi; Maryam Keshavarz; Maryam Ezati; Fatemeh Sarvi (BMC, 2023)
Abstract Background This study aims to investigate the effect of Pilates exercises on sleep and fatigue among female college students residing in the dormitory. Methods This quasi-experimental study, two parallel groups was performed on 80 single female college students (40 per group), between 18 to 26 years old who lived in the two dormitories. One dormitory was considered as the intervention group and another as the control group. The Pilates group received three one-hour Pilates exercise sessions per week for eight weeks and the control group maintained their routine activities. The Pittsburgh Sleep Quality Index (PSQI) and the Multidimensional Fatigue Inventory (MFI-20) were used respectively to assess sleep quality and fatigue levels, at three time points: baseline, end of week four, and eight follow-ups. Fisher's exact, Chi-square, independent sample t-test and repeated measurements were used. Results Overall, 66 participants completed the study (32 and 35 participants in the Pilates and control groups, respectively). After four and eight weeks of intervention, the overall mean score of sleep quality improved significantly (p < 0.001). At week four of the intervention, the Pilates group had a significantly lower mean score for subjective sleep quality and daytime dysfunction than the control group (p < 0.001 and p < 0.002, respectively), although sleep duration and habitual sleep efficiency improved after eight weeks of intervention (p < 0.04 and p < 0.034, respectively). Additionally, the overall mean score of fatigue and its dimensions in weeks four and eight of the intervention in the Pilates group were significantly lower compared to the control group (p < 0.001). Conclusion After eight weeks of Pilates exercises implementation, most components of sleep quality significantly improved; however, the effect of Pilates exercises on fatigue was evident from week four onward. Trial registration This trial was registered on 2/6/2015 in the Iranian Registry of Clinical Trials with the IRCT ID: IRCT201412282324N15. URL of registry: https://www.irct.ir/trial/1970 .